STUDI KOMPARATIF KEABSAHAN WALI NIKAH TERHADAP ANAK HASIL PERNIKAHAN SIRI PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA: (Studi Kasus di KUA Kecamatan Wonosalam Jombang) - Muhammad Choirun Naja; Muhammad (Kampus Akademik Publiser, 2024)
This research aims to analyze andcomparethe validityof marriage guardians for children from unregistered marriages from the perspective of Islamic law and positive law in Indonesia. Unregistered marriages, which are generally not officially recorded in the state's administration, lead to various legal implications, especially regarding the status and rights of childrenbornfrom such marriages. The research method used is a qualitative method with a normative juridical approach. Data was obtained through literature studies from various classical and contemporary Islamic legal sources, as well as the prevailing regulations in Indonesia, such as the Compilation of Islamic Law (KHI) and Law Number 1 of 1974 on marriage. Additionally, interviews with Islamic legal experts and legal practitioners were conducted to gain a deep understanding of this topic. The research results show that from the perspective of Islamic law, the validity of marriage guardians for children from unregistered marriages is still recognized as long as the marriage meets the conditions set by Islamic law, such as the presence of ijab and qabul (offer and acceptance) and the presence of valid witnesses. However, in the context of positive law in Indonesia, unregistered marriages are not officially recognized, which results in the legal status of children from such marriages not being recognized by the state. This causes these children to face limitations in civil rights, such as inheritance rights and legal identity recognition. This research concludes that there is a significant difference between Islamic law and positive law in Indonesia in regulating the validity of marriage guardians for children from unregistered marriages. The author recommends harmonizing Islamic law and positive law to ensure legal certainty and the protection of the rights of children from unregistered marriages.